Marketing Planning for Melted Banana Chips - Alya Ega; Simanjuntak, Naomi; Siallagan, Selvia Santa Maria; Saragih, Lenti Susana (PT FORMOSA CENDEKIA GLOBAL, 2023)
Marketing Plan for Melted Banana Chips at Lymivi Chips Micro Business. This research aims to determine the marketing plan for the Lymivi Chips melted banana chips microbusiness in 2023 as a business unit that has just been initiated and has brilliant sales. Data analysis uses library study observation techniques and questionnaires. Observation is expressing a direct observation of an object. The company does not implement sales targets. Based on the results of the analysis of internal and external factors by maximizing strengths and exploiting existing opportunities as well as minimizing weaknesses and threats from outside by improving the quality of melted banana chips products and services to consumers, looking for potential new supplier areas, promotion via the internet and mass media and additional personnel as a company salesperson, and if you buy fishing rods you get free shipping. The strategy implemented by the company is a marketing mix strategy which consists of a product strategy using a packaging system using plastic vacuum, a pricing strategy based on competitor prices, and the main selling price for determining the selling price of melted banana chips, the company's distribution strategy through local sales around the fishing line, company promotion strategy with a good company name and through social media.